An in vivo approach to the reported effects of phenolic acids and flavonoids on the pancreatic α-amylase activity. (February 2023) - Tonsic, Bárbara Ribeiro; Correa, Vanesa Gesser; Garcia-Manieri, Jessica Amanda Andrade; Bracht, Adelar; Peralta, Rosane Marina
Abstract: Reduction in the activity of the α-amylases which hydrolyze starch and glycogen has been proposed for diminishing the incidence of obesity and diabetes. Many plant extracts contain inhibitors of α-amylases and α-glucosidases and several molecules with this activity have been identified. The present work attempts at investigating if several natural compounds (flavonoids and phenolic acids) that have been reported to be inhibitors of those hydrolytic enzymes can also inhibit starch absorption in vivo . The starch tolerance test in mice was used for assaying starch absorption after administration of 100 mg/kg of five flavonoids (epicatechin, catechin, rutin, quercetin, naringenin) and five phenolic acids (gallic, syringic, vanillic, sinapic, ferulic), which are known in vitro inhibitors of α-amylases. Among the flavonoids, only rutin inhibited starch absorption in mice, even though its effect was only 33% of that one found for the positive control acarbose. Among the five phenolic acids tested only syringic acid produced a clear diminution in starch absorption, which was 47% of that one found with acarbose. On the other hand, other three phenolic acids, namely gallic, sinapic and ferulic acid, caused delay in the absorption of starch, which was characterized by a shift in the time peak of maximal blood glucose concentration, with no modification in the excess of glucose that effectively entered the circulation. Attempts at detecting eventual synergisms by administrating mixtures of flavonoids and phenolic acids were unsuccessful. These results recommend careful translation of in vitro data on the inhibition of α-amylases and α-glucosidases to the in vivo conditions.